Effect of metal ion (Cu, Zn, Sn) precursors on structural and electrical properties of copper zinc tin selenide (Cu2ZnSnSe4) synthesized via solvothermal approach - Shitu, Ibrahim Garba; Katibi, Kamil Kayode; Amusa, Abiodun Abdulhameed; Muhammad, Aminu; Suleiman, Azimov Abdugani Mutalovich; Babani; Tafida, Rabiu Abubakar; Ismail, Usman Idris; Aljfairi, Khaled; Aliyu, Salihu Muhammad; Zakar, Muhammad Nasiru; Isah, Adam Ahmad (Springer, 2026)
In this study, copper–zinc–tin selenide (CZTSe) was synthesized by a solvothermal route chosen for its cost-efficiency, operational simplicity, and capacity to yield highly crystalline products. Ethylenediamine supplied an alkaline environment that promoted CZTSe formation. To clarify the effect of precursor concentration on phase purity, the molar amounts of CuCl2·2H2O, Zn(CH3COO)2·2H2O, and SnCl4·5H2O were varied independently in three separate experiments. X-ray diffraction confirmed the formation of single-phase tetragonal CZTSe, and X-ray fluorescence analysis verified an almost ideal Cu\:Zn\:Sn\:Se stoichiometry of 2:1:1:4. Raman spectroscopy provided additional evidence of phase purity. Field-emission scanning electron microscopy showed that the precursor concentration strongly influenced particle morphology. Electrical conductivity increased with higher CuCl2·2H2O and Zn(CH3COO)2·2H2O levels but declined at elevated SnCl4·5H2O concentrations, the latter attributable to secondary SnO2 formation. These findings demonstrate that the relative concentrations of metal-ion precursors decisively govern the phase evolution, microstructure, and electronic properties of solvothermally synthesized CZTSe.